Luis I. PRÁDANOS, "Postgrowth Imaginaries: New Ecologies and Counterhegemonic Culture in Post-2008 Spain". Liverpool, Liverpool University Press, 2018, 240 pp. - Marrero Henríquez, José Manuel (Tropelías. Revista de Teoría de la Literatura y Literatura Comparada, 2020)
Reseña de Luis I. Prádanos, Postgrowth Imaginaries: New Ecologies and Counterhegemonic Culture in Post-2008 Spain. Liverpool, Liverpool University Press, 2018, 240 pp.